2019
DOI: 10.1186/s40364-019-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune biomarkers in thymic epithelial tumors: expression patterns, prognostic value and comparison of diagnostic tests for PD-L1

Abstract: BackgroundImmunotherapy is currently under investigation in B3 Thymoma (TB3) and Thymic Carcinoma (TC). PD-L1 expression has been evaluated on a limited number of patients with selected antibodies. We aimed to analyze cohort of TB3 and TC with a panel of antibodies to assess the prevalence of PD-L1 expression, its prognostic value and to set up a reproducible test.MethodsWe retrospectively studied 103 patients samples of FFPE histologically confirmed TB3 (n = 53) and TC (n = 50) by expert pathologists within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
7
29
0
Order By: Relevance
“…Although we also performed PD-L2 staining using the same antibody, no staining was observed in our study, corresponding to their results 19 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although we also performed PD-L2 staining using the same antibody, no staining was observed in our study, corresponding to their results 19 .…”
Section: Discussionsupporting
confidence: 82%
“…However, little is known about the clinicopathological signi cance of PD-L2 expression in patients with TETs. Recently, Rouquette et al reported that the PD-L2 antibody stained no tumor epithelial cells in TETs 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, superior vena cava thrombosis in 6.6 % of patients while pneumonia in 6.6 % of patients. However, thromboembolism of small pulmonary arteries in 6.6 % of patients [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…The superior vena cava syndrome (SVCS) was first described in 1757 [1,2]. Reduced blood flow in the superior vena cava (SVC) system decreases the amount of venous blood in the right auricle, causing a number of clinical characteristics and symptoms, such as dilated neck veins, oedematous upper limbs, cyanosis, headache, dyspnoea, cough, and dysphagia [3,4]. Impaired blood flow may be caused by external compression, direct tumour invasion, thrombosis, or ineffective venous return as a consequence of diseases affecting the right auricle or the vessel lumen itself.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the PD-L2 expression was positive in 41 patients (58.6%). However, Isabelle Rouquette et al found that PD-L2 antibody stained no thymic epithelial tumors [15] . Different antibody and cutoff values vary among studies.…”
Section: Discussionmentioning
confidence: 99%